SOCIAL REALISM AND IDEOLOGY IN THE NOVELS OF RICHARD WRIGHT AND SEMBENE OUSMANE (1983)
This study is an attempt at Ideological criticism of black literature. It is divided into five chapters. Chapter one describes briefly the realist tradition in relationship to Richard Wright and Sembene Ousmane. A detailed study is made of the evolution of the concept of realism in literature from the nineteenth century in France to modern times. It is thus possible to locate where our novelists stand on this extensive scale of literary value. While it is possible to document Richard Wright’s indebtedness to realist writer of the American mainstream, Theodore Dreiser as well as the philosophy of existentialism, it is also possible to relate Sembene Ousmane’s aesthetics to that of the socialist realism as well as African oral tradition. The second chapter firmly places the two writers within black literary and social traditions. It examines the black condition which was born out of slavery, racism and colonialism and examines the reactions of Wright and Ousmane to the black condition. While the first two chapters derive from extra literary sources, chapters three to five are strictly based on a stylistic analysis of some of the novels written by Wright and Ousmane. Chapter three concludes that existentialist thought is the main-spring of the Wrightean oeuvre after tracing a vital existentialist link between the major novels of the sane author. On the other hand, the following chapter examines the ways in which the formal structures of Sembene Ousmane’s novels point to the marxist ideology which permeates the texts, thus making them out as socialist realist novels. The comparative perspective is introduced to the study in chapter five where, through a comparison and contrasting of the formal aspects in the works of the two writers, one arrives at the conclusion that despite noticeable divergencies, what unite them is their strict commitment to the black condition, as well as their social realism. In the same chapter, it becomes clear that the ideology of the author is al so transparent through the formal aspects of the novels for while the inner texture of Wright’s novels show him as a critical or "bourgeois" realist that of Sembene Ousmane’s novels prove that the writer is a socialist realist writer. Finally the study illuminates the basis of the works of these two novelists not only as individual writers but as authors who create within a wider tradition of black literature. What have been postulated in the previous chapters for their novels become even more relevant for black literatures in general.